Principals’ Leadership Style towards the Implementation of Decentralized School-Based Management in Selected Secondary Public Schools in Mandaluyong City, Philippines - Ryan Jay C. Verbo; Aljon I. Fernando; Wendell C. Cabrera (Yayasan Riset dan Pengembangan Intelektual, 2023)
The purpose of the conduct of this study was to identify the leadership styles of the school heads in implementing school-based management. Likewise, it also aimed to determine the relationship between the leadership styles of the principals and its current SBM level of practice. The study was undertaken in eleven (11) public secondary schools in Mandaluyong City with fifty-five (55) teacher-respondents who are members of their respective SBM team. The mixed method design was used in the study. Correlational method of research was used to determine the relationship between the leadership styles and the corresponding current SBM level of practice. Survey questionnaire was utilized to identify the perceived leadership styles demonstrated by the principals in implementing SBM. An interview through focus group discussion was conducted to determine how leadership styles of the school heads affect the implementation of school-based management. As revealed in the results of the study, most of the members of the SBM team in each school perceived that Transformational leadership, Transactional leadership, Strategic leadership, and Democratic leadership are the frequently leadership styles employed by the principals in the implementation of the school-based management. Likewise, since the computed value 22.00 using the chi-square test is greater than the tabular value 18. 307 at 0.05 alpha and 10 degrees of freedom, the null hypothesis was rejected and concludes that there is a significant relationship between the principals’ leadership style and the status of the SBM level of practice. Most of the participants of the study perceived that leadership styles of the principals directly affect the performance of the whole team in achieving the status of SBM level of practice. A school head with a strong leadership would mean significant and better results as to compare to a school head who most of the time delegated the tasks directly to his team.